'Fragmented, parochial, and specialised'?: the history curriculum in Australian and New Zealand universities. Issue 2 (3rd April 2019) - Sendziuk, Paul; Crotty, Martin
Abstract: This article reports the findings of a comprehensive survey of the History curriculum taught at 44 universities in Australia and New Zealand. It reveals the fields of History that were most commonly offered in 2016, as well as how many students took courses in particular fields. The results for Introductory and Upper level courses (which serve different purposes) are separated, and the results from each country, and 'Group of Eight' (Go8) and non-Go8 universities within Australia, are compared. The findings dispute recent contentions by the Institute of Public Affairs that the university History curriculum is 'fragmented, parochial, and specialised' or unduly influenced by 'identity politics'. By comparing the findings with the results from similar surveys undertaken in the mid-1990s and 2004, the article also suggests ways in which the curriculum and student enrolments have evolved over the past two decades.